2002
DOI: 10.1007/bf03345104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of progesterone (P) and antiprogestin RU486 on LH and FSH release by incubated pituitaries from rats treated with the SERM LY117018-HCl and/or recombinant human FSH

Abstract: The aim of the present study was to investigate the role of the estrogen (ES) background on the effects of P or its antagonist RU486 on basal and LHRH-stimulated LH and FSH secretion. To do this, pituitaries collected from: intact rats in proestrus; rats injected with the ES antagonist LY11701 8-HCl; rats injected with recombinant-human FSH (r-hFSH) to stimulate ovarian hormonogenesis; and rats injected with both LY11701 8-HCl and r-hFSH were incubated with or without LHRH (10 nM) in the presence of P (100 nM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…At the level of the pituitary gland, progesterone has been shown to regulate the magnitude and possibly the duration of the preovulatory gonadotropin surge (Banks and Freeman 1978; Krey and Kamel 1990; Turgeon and Waring 1990). In agreement with these results, Bellido et al (2002) reported that LH and FSH secretion were reduced by application of the antiprogestin RU486 to isolated pituitaries. As RU486 reduces galanin (Sanchez-Criado et al 2001) and activin (Szabo et al 1998) stimulating effects on LH and FSH secretion, progesterone treatment appears to exert direct effects on the pituitary.…”
Section: Discussionsupporting
confidence: 63%
“…At the level of the pituitary gland, progesterone has been shown to regulate the magnitude and possibly the duration of the preovulatory gonadotropin surge (Banks and Freeman 1978; Krey and Kamel 1990; Turgeon and Waring 1990). In agreement with these results, Bellido et al (2002) reported that LH and FSH secretion were reduced by application of the antiprogestin RU486 to isolated pituitaries. As RU486 reduces galanin (Sanchez-Criado et al 2001) and activin (Szabo et al 1998) stimulating effects on LH and FSH secretion, progesterone treatment appears to exert direct effects on the pituitary.…”
Section: Discussionsupporting
confidence: 63%
“…While many reports have been on women undergoing ovarian stimulation, GnSIF/AF activity has also been found in follicular fluid from naturally cycling women (Fowler et al, ). Several reports indicated that one of GnSIF/AF's major actions is to maintain the pituitary in a state of low‐sensitivity to GnRH during the early‐ and mid‐follicular phase, and that this effect is augmented by estrogen and progesterone (Byrne et al, ; Byrne et al, ; Tijssen et al, ; de Koning et al, ; Bellido et al, ; Gordon et al, ). One group described FSH as having two effects on LH secretion: stimulating production of GnSIF/AF and directly affecting the pituitary (Hull et al, ).…”
Section: Evidence For Gnsif/afmentioning
confidence: 99%